2015
DOI: 10.1007/s11606-014-3166-5
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy, Vulnerable Patients, and Health Information Technology Use: Where Do We Go from Here?

Abstract: In the past few years, the rapid adoption of health information technology (HIT) in the US has been very apparent, largely driven by the more than $25 billion in incentives for "Meaningful Use" of HIT provided to date as a part of healthcare reform in the Health Information Technology for Economic and Clinical Health (HITECH) Act. As we move into Stage 2 of the Meaningful Use program with new metrics for patient engagement, healthcare leaders are now shifting their focus from implementation to understanding pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…A large proportion of individuals in our study, even those who used the computer or mobile phone for other tasks, reported that the portal seemed too complex to access. This is consistent with previous evidence that documented lower usability of portal websites among racial/ethnic minority patients as well as those with limited health literacy [ 20 , 21 ]. Moreover, the need for health literacy training or support was also evident, such as the lack of confidence in being able to independently interpret medical content presented on a portal without one-on-one assistance, which is also consistent with other health technology work [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…A large proportion of individuals in our study, even those who used the computer or mobile phone for other tasks, reported that the portal seemed too complex to access. This is consistent with previous evidence that documented lower usability of portal websites among racial/ethnic minority patients as well as those with limited health literacy [ 20 , 21 ]. Moreover, the need for health literacy training or support was also evident, such as the lack of confidence in being able to independently interpret medical content presented on a portal without one-on-one assistance, which is also consistent with other health technology work [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…A lower subjective health literacy is associated with less perceived information provision and lower information satisfaction [ 39 , 40 ]. To comprehend written health information, a person must have certain reading and health literacy levels [ 41 ]. HNC patients are known to have lower educational levels [ 42 ], have poor health literacy, have difficulties interpreting commonly used written health information, feeling inadequately informed.…”
Section: Discussionmentioning
confidence: 99%
“…Further, many studies define vulnerability in relation to isolated characteristics such as socioeconomic characteristics [8] , self-reported health literacy [17] or ethnicity [18] . However, these characteristics may not adequately capture the concept of vulnerability [19] . A vulnerable population in general has been described as a disadvantaged sub-segment of the community, requiring utmost care and consideration [20] .…”
Section: Introductionmentioning
confidence: 99%